PENGEMBANGAN MODUL PJOK TEKNIK DASAR BULU TANGKIS BERBANTUAN QR-CODEKELAS VIII SMP BK (BAKTI KELUARGA) KOTA LUBUKLINGGAU - Wawan Syafutra; Taufik Hidayat (Jurnal Tunas Pendidikan, 2022)
ABSTRACT This study aims to develop a PJOK module on the basic Qr-Code rock badminton technique for class VIII SMP BK (BaktiKeluarga) Lubuklinggau and to determine the quality of the module from the aspect of validity and practicality. This research is a development research that refers to the development of the ADDIE model, namely Analysis (Analysis), Design (design/design), Development (Development), implementation (implementation/execution), and Evaluation (evaluation/feedback). The evaluation stage was not carried out because of the time in the study. The instruments used to measure the quality of the modules developed include validation, practicality questionnaires with an average score of . The product of this research is in the form of a basic badminton technique material module with the help of Qr-Code for class VIII junior high school students. The results showed that: (1) The results of the assessment determined by the three validators/experts (media, language, material experts) linguists were categorized as quite valid with v total media experts 0.64 categorized as "High Enough, v total linguists 0 .62 was categorized as “High Enough”, and material experts with a total v of 0.54 were categorized as “Enough”.(2) the quality is seen from the practical aspect, the practical category of the one-to-one test with an average score of 4.0 is categorized as Very Practical and the small group with an average score of 4.2 is categorized as Very Practical. Keywords: Badminton material module